PENERAPAN PRINSIP HIDUP KAMASE-MASEA MASYARAKAT ADAT AMMATOA KAJANG, BULUKUMBA SULAWESI SELATAN DALAM PENGELOLAAN SUMBER DAYA ALAM - Disnawati, Disnawati (Sabda: Jurnal Kajian Kebudayaan, 2013)
The community ofAmmatoa in Kajang have faith to "Pasang" which teaches them to live in simplicity, as the principle of Kamase-masea. Pasang contains the rules that regulate the relationship between humans and God, among human beings, and humans with nature. They are very obedient to preserve the environment, especially their forests. Forest management practice based on "Pasang" is an interesting phenomenon, because certain part of the Pasang actually implements conservation practices and sustains forest management.